Teach yourself visually HTML 5 - Wooldridge, Mike (Wiley Pub., 2011)
HTML5 is the next-generation of web standard mark-up language, and among other things, it offers amazing new avenues for incorporating multimedia into your sites. What easier way to master all of HTML5's new bells and whistles than with a guide that shows you, screenshot by screenshot, just what to do? Over a hundred tasks that web designers need to know most are explained using, full-color screenshots and how-to steps. From the easy stuff like revised new header and footer elements to complex updates such as canvas and audio, this guide covers the new, as well as most-commonly used, tags and features.